Balinese Language Usage by Ethnic Bali Teens in Dangin Puri Village, East Denpasar Subdistrict, Denpasar City - Ni Putu Geasha Pusvika Devi; Ni Wayan Kasni (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2018)
This study examines the use of Balinese language by ethnic Balinese teenagers based on the language use domains that have been determined by the author, and also the factors that influence the use of Balinese language by ethnic Balinese teenagers in the village of Dangin Puri, East Denpasar district, Denpasar City. The method used in this research is qualitative and quantitative method. This research data in the form of primary data taken from the field in the form of the use of the language of Bali by teenagers, and secondary data in the form of writing data obtained from the questionnaire. The results of this study indicate that the use of Balinese language by ethnic Balinese teenagers in the village of Dangin Puri based on four domains that have been determined that the family, the neighborhood, the domain of education, and the domain of religion are still quite high. Factors influencing the use of Balinese language by ethnic Balinese teenagers are caused by internal factors that include self-factor, interaction factor in the family, and factor interaction with the environment and friends, then external factors that influence the condition of bilingual speakers, the factors of globalization, educational factors, and Indonesian factors.